(untitled) (Journal of Economics and Sustainability, 2019)
When encountering a business environment characterised with rapid changes, the manufacturing industry needs to emphasise knowledge management to enhance organisational performance. Knowledge management represents the processes and practices carried out in organisations to leverage their intellectual potential by enhancing the effectiveness and efï¬ciency of their knowledge resources. A growing number of studies have demonstrated that knowledge management is related to organisational performance. However, the practice of knowledge management is not prevalent in many developing countries even though it has been claimed to be an essential component to enhance organisational performance. The purpose of this study was to examine the association of knowledge management and organisational performance using survey data obtained from 185 respondents in electrical and electronic (E&E) manufacturing firms in Malaysia. Partial least squares structural equation modelling (PLS-SEM) was used to test the research hypothesis. The finding indicated a significant relationship between knowledge management and organisational performance. The result provides empirical evidence that it is imperative for business firms to manage their knowledge resources to enhance their organisational performance. Practical implications of the research finding for E&E manufacturing firms are discussed.